Potential of biodiesel as a renewable energy source in Bangladesh. (October 2015) - Habibullah, M.; Masjuki, H.H.; Kalam, M.A.; Rahman, S.M. Ashrafur; Mofijur, M.; Mobarak, H.M.; Ashraful, A.M.
Abstract: The transportation, agricultural, and power sector of Bangladesh is largely dependent on fossil fuels that decrease day by day. The government has to import large volumes of fuel from foreign sources to meet the fuel demand for power production, causing a negative impact on the country's economy. Finding an alternative to fossil fuels is becoming the most urgent issue. Biodiesel can thus be a destined source to future energy demands. Increasing the usage of biodiesel will also decrease the global problem of environmental pollution, as fossil fuels are considered to be the major source of harmful emissions. Biodiesel is renewable, bio-degradable, non-toxic, technologically feasible, and can be used as a bio-lubricant. In this study, the current energy scenario of Bangladesh, available potential biodiesel feedstocks, production process and engine fuel property, environmental impact, performance and emission characteristics on diesel engines, comparison of cost analysis, and future direction are discussed. Various research related to these feedstocks are performed in Bangladesh, which include an overview of biodiesel properties, engine performance, and emission parameters used in diesel engines. All types of biodiesel have similar functional properties compared with diesel fuel and can be successfully used in compression ignition engines. Biodiesel can thus serve as a subsequent replacement of non-renewable fossil fuels. Compared with diesel fuel, CO and HC emission were also low, but a slight increase in NO x was observed in some cases. One of the major advantages is that Bangladesh is a country with plenty of biodiesel feedstock sources, such as mustered, Jatropha curcas, rapeseed, sesame, castor, cottonseed, neem, algae, coconut, and groundnut. In conclusion, producing biodiesel from different feedstocks is greatly possible and can thus assist in future energy needs.